A model-based framework for the quality assessment of surface albedo in situ measurement protocols. (September 2016) - Adams, Jennifer; Gobron, Nadine; Widlowski, Jean-Luc; Mio, Corrado
Abstract: Satellite-based retrievals of land surface albedo are essential for climate and environmental modelling communities. To be of use, satellite-retrievals are required to comply to given accuracy requirements, mainly achieved through comparison with in situ measurements. Differences between in situ and satellite-based retrievals depend on their actual difference and their associated uncertainties. It is essential that these uncertainties can be computed to properly understand the differences between satellite-based and in situ measurements of albedo, however quantifying the individual contributions of uncertainty is difficult. This study introduces a model-based framework for assessing the quality of in situ albedo measurements. A 3D Monte Carlo Ray Tracing (MCRT) radiative transfer model is used to simulate field measurements of surface albedo, and is able to identify and quantify potential sources of error in the field measurement. Compliance with the World Meteorological Organisation (WMO) requirement for 3% accuracy is tested. 8 scenarios were investigated, covering a range of ecosystem types and canopy structures, seasons, illumination angles and tree heights. Results indicate that height of measurement above the canopy is the controlling factor in accuracy, with each canopy scenario reaching the WMO requirement at different heights. Increasing canopy heterogeneity and tree height noticeably reduces the accuracy, whereas changing seasonality from summer to winter in a deciduous forest increases accuracy. For canopies with a row structure, illumination angle can significantly impact accuracy as a result of shadowing effects. Tests were made on the potential use of multiple in situ measurements, indicating considerably increased accuracy if two or more in situ measurements can be made. Abstract : Highlights: We present a model-based framework for the quality assessment of in situ albedo. 3D Monte Carlo model simulates in situ field measurements in complex 3D canopies. The height and placement of albedometer are controlling factors in uncertainty. Uncertainties depend on ecosystem type and canopy structure, season and solar angle. Multiple in situ albedo measurements can significantly reduce uncertainty.